Reframing services for Malaysian students in schools: time to bring occupational therapy into the classroom - Masne Kadar,; Nor Afifi Razaob,; Hany Naziha Mohd Saibani,; Chai, Siaw Chui; Noorashikin Samin, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Autism spectrum disorder is a developmental disability that has gained increasing attention in Malaysia. Much effort is now being taken to include children with autism spectrum disorder in the school system, either in inclusive settings or in special educational settings. However, this endeavor raises many challenges for the children with autism spectrum disorder, their families and for service providers. The current study uses a qualitative approach to investigate parents’ perceptions of problems faced by their children with autism spectrum disorder in issues related to academic skills. A face-to-face interview was performed with parents of children with autism spectrum disorders who were receiving occupational therapy services for their difficulties in academic related skills. Findings indicate that most of the difficulties faced by these children are related to skills needed to be accepted at school, such as ability to communicate and socialize and this often limit their performance at school. These findings not only raise and discuss important implications for service providers such as teachers, health care professionals and policy makers, but also lead to suggestions for future research.